Diverse Roles and Academic Performance of Tertiary Students in Masvingo, Zimbabwe - Lokadhia Manwa (STKIP Singkawang, 2020)
Tertiary student roles are a critical aspect of student life during their academic career as they significantly contribute to the success of the whole learning process and the accomplishment of the entire course. This study contributes to debates on the influence of student multiple roles on academic engagement given the limited research on this phenomenon in Africa and Zimbabwe in particular. By investigating the factors influencing the nature of students’ roles, the findings may influence researchers to investigate other aspects of students’ life situations. The study sought to explore from the students’ perspectives, how they juggle their roles and from lecturers how these students perform. A qualitative approach that employed convenient sampling used twenty-one students and six lecturers from the three tertiary institutions in the city. Open-ended questionnaires and in-depth face-to-face interviews were used to generate data from the participants. Thematic analysis was used to process data, whereby common ideas and patterns that came up repeatedly were coded leading to key issues. Factors such as family background, family life cycle stage and economic status were found to be influencing the nature of students’ roles. Students indicated that they occupy many social roles which they could not ignore. They also reported negative effects of these roles on academic engagement. Lecturers also indicated that most students were not performing to their best. The study, therefore, recommends serious consideration of the various interplay underpinning factors that may impact negatively on student role behaviour. The incorporation of time-management and ingenuity into the university curriculum may benefit all students.